Identifikasi Drug Related Problems Pada Pasien Congestive Heart Failure di Rumah Sakit “X” Balikpapan: Identification of Drug-Related Problems in Patients with Congestive Heart Failure at “X” Hospital Balikpapan - Esa Wi Fatma; Nur Masyithah Zamruddin; Adam M. Ramadhan (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Heart failure is a condition where the heart fails to pump blood to meet the needs of the tissues. CHF patients are generally given at least 4 types of drugs, namely ACEIs, beta blockers, diuretics and digoxin. As a result, if it is not considered properly, it will be detrimental to the patient. This study is a non-experimental observational study with retrospective data collection on medical record data of patients who meet the inclusion criteria with the aim of knowing patient characteristics, knowing the description of drug use and knowing the incidence of DRPs in CHF patients at Hospital "X" Balikpapan. The results obtained from 106 patients, male patients were taller than female by 68 patients (64.15%), the highest age was in the late elderly category (56-65 years) as many as 40 patients (37.73%), the highest comorbid namely HHD 31 patients (29.24%), VES 16 patients (15.10%), renal insufficiency 13 patients (12.26%) and hypokalemia 13 patients (12.26%). The description of drug use in CHF patients included aspirin in 77 patients (72.64%), furosemide 62 patients (58.49%) and bisoprolol 49 patients (46.22%). The incidence of DRPs in the drug interaction category was 88 patients (83.01%), indicated without drugs 10 patients (9.43%), drugs without indications 4 patients (3.77%), inaccuracy of drug selection 2 patients (1.88%) , and failure to receive medication in 1 patient (0.94%), no incidence was found in the low dose, over dose and ADR categories.